Development of a New LAMP Assay for the Detection of Ancylostoma caninum DNA (Copro-LAMPAc) in Dog Fecal Samples - Avila, Héctor Gabriel; Risso, Marikena Guadalupe; Cabrera, Marta; Ruybal, Paula; Repetto, Silvia Analía; Butti, Marcos Javier; Trangoni, Marcos David; Santillán, Graciela; Pérez, Verónica Mirtha; Periago, María Victoria (Frontiers in Veterinary Science, 2021)
Ancylostoma caninum is a zoonotic nematode which is able to affect animals and humans. Diagnosis in the definitive host and environmental detection are key to prevent its dissemination and achieve control. Herein, a new coprological LAMP method for the detection of A. caninum (Copro-LAMPAc) DNA was developed. DNA extraction was performed using a low-cost method and a fragment of the cox-1 gene was used for primer design. The analytical sensitivity, evaluated with serial dilutions of genomic DNA from A. caninum adult worms, was 100 fg. A specificity of 100% was obtained using genomic DNA from the host and other pathogens. The Copro-LAMPAc was evaluated using environmental canine fecal samples. When compared with gold standard optical microscopy in epidemiological studies, it proved to be more sensitive. This new LAMP assay can provide an alternative protocol for screening and identification of A. caninum for epidemiological studies in endemic areas.